2016
DOI: 10.1016/j.canlet.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta as target for colorectal cancer prevention

Abstract: Colorectal cancer (CRC) is a leading cause of death in the United States. Despite its slow development and the capacity for early diagnosis, current preventive approaches are not sufficient. However, a role for estrogen has been demonstrated in multiple epidemiologic studies, which may benefit CRC prevention. A large body of evidence from preclinical studies indicates that expression of the estrogen receptor beta (ERβ/ESR2) demonstrates an inverse relationship with the presence of colorectal polyps and stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 96 publications
8
113
0
1
Order By: Relevance
“…Similar data have been previously reported for different types of tumors, both related and unrelated to the reproductive system (111119). …”
Section: Estrogen Receptor β and Melanomasupporting
confidence: 90%
See 1 more Smart Citation
“…Similar data have been previously reported for different types of tumors, both related and unrelated to the reproductive system (111119). …”
Section: Estrogen Receptor β and Melanomasupporting
confidence: 90%
“…These compounds have been suggested as possible effective agents in the prevention of several diseases, such as menopausal symptoms, osteoporosis, and cardiac diseases (145). They have also been reported to exert antitumor activity on different types of cancers, based on their high affinity binding to ERβ and their ability to increase the expression of this receptor subtype (115, 119, 138, 146148) (Table 1). …”
Section: Natural Erβ Ligands and Melanomamentioning
confidence: 99%
“…Further, estrogen through estrogen receptor β (ERβ/ESR2) appears to reduce the risk of CRC development (reviewed in []). Our previous cell‐based analyses have shown that re‐introduction of ERβ into CRC cells exhibits anti‐proliferative functions, represses oncogenes, and mediates anti‐inflammatory signaling .…”
Section: Introductionmentioning
confidence: 99%
“…The loss of expression of ER β is inversely correlated with more advanced Dukes' staging in colon cancer [9]. Cellular experiments supported the tumor suppressive effect of ER β in colon [10]. From the phenotype of ER β −/− mice, there is more colitis-associated neoplasia [11] and ERβ in the colon appears to decrease proliferation and increase apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%